KEMAMPUAN PEMAHAMAN KONSEP MAHASISWA PADA MATA KULIAH STRATEGI BELAJAR MENGAJAR MATEMATIKA DI TINJAU DARI STRATEGI PEMBELAJARAN - Rini Utami (LPPM Universitas Pekalongan, 2017)
This study aims to determine differences in the ability of understanding the concept of students in terms of learning strategies are implemented, if there is a difference then see which one was the best of all strategy applied learning course of Mathematics Teaching and Learning Strategies. This research is a quantitative research with experimental method. The instrument uses test the ability of understanding of the concept. Analysis of data one way Anova with SPSS. The result of the reasearch with one way Anova test showed that difference of students concept comprehension ability. Understanding the concept of students with strategies information search is not the same as the strategy everyone is teacher here. The strategy of information search is not the same as the strategy of learning start with a question and strategies everyone is teacher here at with learning start with a question. If the views of average ability students' understanding of concepts, information search strategy is better than the strategy everyone is techer here.